Infectious complications after liver transplantation in human immunodeficiency virus‐infected recipients. Issue 5 (26th September 2015) - Teicher, E.; Boufassa, F.; Vittecoq, D.; Antonini, T.M.; Tateo, M.‐G.; Coilly, A.; Roque‐Afonso, A.‐M.; Kassis‐Chikhani, N.; Lambotte, O.; Ichai, P.; Samuel, D.; Duclos‐Vallee, J.‐C.
Abstract Background Few studies have investigated infections in human immunodeficiency virus (HIV)‐infected liver transplant patients. The aim of this study was to describe the prevalence, time of onset, mortality of infectious complications, other than hepatitis C virus (HCV), and to identify risk factors for their development in a large single‐center cohort of HIV‐infected liver transplant patients. Methods We studied 109 consecutive HIV‐infected patients who underwent liver transplantation (LT) between 1999 and 2010 and followed until December 2012. Results The median age was 44 years (interquartile range [IQR] 41–49), 82.6% were male, and the median follow‐up was 45.7 months (IQR 14–65). The major indications for LT were HCV cirrhosis (61%) and hepatocellular carcinoma (19%). Forty patients (37%) developed at least 1 infection during the first year after LT. Twenty‐eight (26%) patients had an episode of bacteremia. Five (4.6%) patients developed a cytomegalovirus infection. Fungal infections occurred in 5 (4.5%) patients. Four (3.6%) patients developed an HIV‐related opportunistic infection. A total of 43 (39.4%) patients died during follow‐up. Mortality related to infection occurred in 9 (7%) cases, and 20 (42.5%) patients died because of HCV recurrence. No patients died from opportunistic infections. Model for end‐stage liver disease (MELD) score >17 was associated with a 2‐fold higher risk (hazard ratio 1.96; 95% confidence interval 1.01–3.80) of developing infectious complications. Conclusions Infections are not a major cause of mortality after LT in HIV patients and opportunistic infections of acquired immunodeficiency syndrome are infrequent. A MELD score >17 increased the risk of developing post‐LT infectious complications. Recurrence of HCV infection remains a major cause of mortality.